A rhodamine based fluorescent probe validates substrate and cellular hypoxia specific NADH expression. Issue 4 (17th December 2018) - Podder, Arup; Koo, Seyoung; Lee, Jiyeong; Mun, Sora; Khatun, Sabina; Kang, Hee-Gyoo; Bhuniya, Sankarprasad; Kim, Jong Seung
Abstract : A novel rhodamine-based redox probe (MQR ) was developed to visualize the alteration of the NADH level under diverse metabolic perturbations. Abstract : Herein, we report a rhodamine-based redox probe (MQR ) to visualize cytosolic NADH in the cellular milieu. Its high sensitivity and selectivity allowed it to track the alteration of the NADH level under metabolic perturbation, suggesting its potential as a useful tool to study the association between the NADH level and metabolic abnormalities with clinical significance.